2021
DOI: 10.1111/jvim.16079
|View full text |Cite
|
Sign up to set email alerts
|

Influence of endocrine disease on l‐lactate concentrations in blood of ponies

Abstract: Background: Blood l-lactate concentrations are higher in people with developing or established diabetes mellitus and insulin resistance. Objectives: To investigate whether blood l-lactate concentrations are positively correlated with measures of insulin dysregulation (ID) or increased autumnal ACTH concentrations in ponies. Animals: Systemically healthy client-owned ponies (n = 101). Methods: Prospective case-control study. Blood samples were obtained from 101 clinically healthy ponies. Breed, weight, height, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…41 In a pilot study of 90 horses with acute gastrointestinal disease admitted to our hospital, 42 ponies had significantly higher median body condition scores than horses, and obese horses and ponies had higher plasma lactate concentrations at admission than lean horses and ponies. Previous studies in healthy horses have shown that plasma lactate concentrations are lower in obese than non-obese ponies 43 and in ponies than horses, 44 and further research is thus needed to understand the effect of obesity on the lactate response in horses.…”
Section: Discussionmentioning
confidence: 99%
“…41 In a pilot study of 90 horses with acute gastrointestinal disease admitted to our hospital, 42 ponies had significantly higher median body condition scores than horses, and obese horses and ponies had higher plasma lactate concentrations at admission than lean horses and ponies. Previous studies in healthy horses have shown that plasma lactate concentrations are lower in obese than non-obese ponies 43 and in ponies than horses, 44 and further research is thus needed to understand the effect of obesity on the lactate response in horses.…”
Section: Discussionmentioning
confidence: 99%